Pengaruh Penggunaan Abu Sekam Padi sebagai Bahan Pengisi pada Campuran Hot Rolled Asphalt terhadap Sifat Uji Marshall - Sri P. Atmaja Rosyidi (Semesta Teknika, 2012)
Rice Husk Ash (RHA) has fairly high content of SiO2 and easily obtainable. It is inexpensive since it is the residual waste of the tile or brick combustion process that is not utilized properly. RHA has the potential to be used as filler in Hot Rolled Asphalt (HRA) since it has high flexibility mixture design. The influential characteristic of RHA is that it has fine aggregate fraction. This study aims to discover the physical properties of RHA, the characteristic of the Marshall test properties, the optimum bitumen content, and the economical comparison between the RHA-mixed HRA and the conventional one using stone dust filler. The results of this study indicate that the use of the RHA is able to increase the optimum bitumen content. In terms of economical comparison, the use of RHA as filler material is much more economical than using stone dust as filler.